Sexuality and fertility desire in a large cohort of individuals with 46, XY differences in sex development (Clinics, 2023)
Objective: To analyze aspects of sexual life and fertility desire among 46, XY DSD people, including those who changed their gender.Methods: It is a cross-sectional study including 127 adults (> 16 years of age) with 46, XY DSD (83 females; 44 males) from a Single Brazilian Tertiary-Care Medical Center.Results: Sexual fantasies and masturbation were more frequent in 46, XY DSD males, whereas orgasm and sexual life satisfaction were similar in both genders. More 46, XY DSD men than women had a long-term romantic relationship. 46, XY DSD women with prenatal androgen exposure reported more fear of being romantically rejected. External genitalia appearance at birth did not impact the sexuality of 46, XY DSD women after surgical genital treatment had been completed. Overall, the sexual life was similar between 46, XY men assigned as males and those who changed to the male gender. Regarding sexual orientation, most self-reported as heterosexual (91% and 92% of women and men, respectively). The desire for fertility had a similar prevalence in both genders, but more women than men considered infertility a barrier to a long-term romantic relationship. Twelve individuals (7 males) had children; 10 out of 12 have adopted children.Conclusion: Fertility desire was shared among 46, XY DSD people, regardless of gender. Prenatal androgen exposure reduced the desire for motherhood in 46, XY women. 46, XY DSD people who changed from female to male gender presented similar sexual parameters as those assigned as males. Among females, virilized genitalia at birth did not affect sexuality once the surgical treatment is completed.